A FACTOR INFLUENCING THE REPURCHASE INTENTION ON TIKTOK FOR BABY BOTTLES - Daniel Pungkas Prastia Wibowo; Daru Putri Kusumaningtyas; Osly Usman; Verry Febriansyah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2026)
This study aims to analyze the factors that influence repurchase intention of baby bottle products through TikTok Shop, focusing on the roles of short video content, customer experience, perceived value, and customer satisfaction. The research uses a quantitative method with purposive sampling, involving 118 respondents who have made at least two purchases via TikTok Shop. Data were collected through an online questionnaire using a six-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that customer satisfaction has the most significant and strong effect on repurchase intention, while short video content, customer experience, and perceived value influence repurchase intention indirectly through customer satisfaction. The model demonstrates high explanatory and predictive power, with R-square values of 0.642 for customer satisfaction and 0.781 for repurchase intention. This study concludes that building customer satisfaction is key to encouraging repeat purchases. Engaging short video content and positive customer experiences contribute significantly to perceived value and satisfaction. The findings highlight the importance of optimizing video-based digital marketing strategies in social commerce platforms like TikTok Shop. Marketers should focus on content that is informative, visually appealing, and relevant to enhance customer loyalty and purchasing decisions.